2022
DOI: 10.1186/s12883-022-02798-9
|View full text |Cite
|
Sign up to set email alerts
|

SLC20A2-related primary familial brain calcification with purely acute psychiatric symptoms: a case report

Abstract: Background Primary familial brain calcification (PFBC) is a rare inherited neurological disorder characterized by bilateral basal ganglia calcification with a series of motor and nonmotor symptoms. Mutations in the SLC20A2 gene, encoding the PiT2 protein, are the major cause of the disease. Here, we report a Chinese PFBC family carrying a SLC20A2 gene mutation, and the proband presented with purely acute psychiatric symptoms, which has been rarely reported in this disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…SLC20A2 is the most common PFBC gene; heterozygous variants have been identified in more than 60% of genetically confirmed PFBC patients [ 3 ]. A missense change is the most common variant type, followed by frameshift, nonsense, and splice site variations, without obvious hotspots for pathogenic variants ( Figure 1 a) [ 3 , 6 , 7 , 17 , 18 , 21 , 23 , 37 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Functionally, both haploinsufficiency and dominant negative effects have been described; the loss of normal PiT2 function results in extracellular Pi accumulation and subsequent calcium phosphate formation [ 6 , 42 ].…”
Section: Genetics and Disease Mechanismmentioning
confidence: 99%
“…SLC20A2 is the most common PFBC gene; heterozygous variants have been identified in more than 60% of genetically confirmed PFBC patients [ 3 ]. A missense change is the most common variant type, followed by frameshift, nonsense, and splice site variations, without obvious hotspots for pathogenic variants ( Figure 1 a) [ 3 , 6 , 7 , 17 , 18 , 21 , 23 , 37 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Functionally, both haploinsufficiency and dominant negative effects have been described; the loss of normal PiT2 function results in extracellular Pi accumulation and subsequent calcium phosphate formation [ 6 , 42 ].…”
Section: Genetics and Disease Mechanismmentioning
confidence: 99%
“…Of note, pontine calcifications are typically overserved in subjects with mutations or MYORG [62]. In subjects with PFBC, serum levels of calcium, parathormone (PRH), and vitamin D were found to be within range [26,41,42,50,51,55,57,[63][64][65][66][67].…”
Section: Primary Familial Brain Calcifications: Clinical Aspectsmentioning
confidence: 99%
“…Currently, pathogenic variants in SLC20A2, PDGFRB, PDGFB, XPR1, MYORG, JAM2, and CMPK2 are known to be genetic causes of PFBC [5]. White matter hyperintensities, presumably of vascular origin, have previously been described in PFBC patients with SLC20A2 [6], PDGFRB [7] and PDGFB [8][9][10] variants, and have been explained by the impairment of pericyte recruitment during angiogenesis leading to vascular dysfunction [8,11]. One previous study has reported alterations in the architecture of extracerebral blood vessels of one patient with PFBC and a pathogenic PDGFB variant [8].…”
Section: Introductionmentioning
confidence: 99%